DECISION-MAKING IN ELDERLY CARE HOMES: BETWEEN SAFETY IMPERATIVES AND THE PROTECTION OF RESIDENTS’ RIGHTS AND FREEDOMS - CATHERINE, Aurore (MEDECINE LEGALE DROIT MEDICAL, 2025)
When making decisions concerning residents, elderly care homes managers are obliged to weigh up a number of potentially conflicting considerations. The rights and freedoms of the elderly can be compromised in the interests of security. The aim of this article is to examine the factors that undermine the decision-making of facility managers, in order to better identify the elements that are essential for further reection on how to promote the observance and quality of the exercise of these rights and freedoms.